Determination of optimal variant for insulation of the attic floor of the educational building - Yurin, Oleg; Zyhun, Alina; Kliepko, Anastasiia; Qiniso, Mahlinza (Academic journal Industrial Machine Building Civil Engineering, 2022)
The analysis of heat-protective properties of the existing attic floor of the educational building of National University «Yuri Kondratyuk Poltava Polytechnic» showed their non-compliance with regulatory requirements. The required thickness of the insulation in the attic floor was determined without taking into account the heat-conducting inclusions. Overlapping areas with heat-conducting inclusions reduce the reduced heat transfer resistance. In the attic floor, these are the areas where the floor adjoins the inner and outer walls. It is possible to increase the reduced heat transfer resistance due to additional insulation of external and internal walls within the cold attic. The study determined the optimal length of additional insulation for eight different options. To determine the optimal value, options for additional insulation of external and internal walls within the attic with a simultaneous reduction in the thickness of the insulation on the attic floor were considered.